Two Approaches for Inter-Satellite Radiometer Calibrations between TMI and WindSat - Hong, Liang; Jones, Linwood W.; Wilheit, Thomas T.; Kasparis, Takis (My University, 2009)
This paper presents recent progress in inter-satellite microwave radiometric cross-calibration to eliminate brightness temperature measurement biases between a pair of radiometer channels operating at slightly different frequencies and incidence angles. The motivation of this research is to develop robust analytical cross-calibration techniques for inter-calibration of various satellite radiometer instruments, with the first projected application being the multi-satellite Global Precipitation Measurement (GPM) constellation to be launched in 2013. The significance of this work is that it will allow the formation of consistent multi-decadal time series of geophysical measurements for multiple satellite microwave radiometers that are free of instrumental biases and other long-term changes in radiometric calibration, which will allow researchers to study global climate change. Descriptions are given for two independent calibration techniques: a Taylor series expansion of the oceanic brightness temperature (Tb) spectrum between dissimilar radiometer channels and a non-linear regression among multi-channel Tb measurements. In the first approach, predictions were made of Tb's at a destination frequency from Tb's of a close by source frequency by expansion of the oceanic brightness temperature spectrum in a Taylor series centered at the source frequency. The relationships between Tb's and frequencies were derived from simulations using a radiative transfer model (RTM), which accounts for the total collected emissions from the ocean surface and the atmosphere. Further, earth incidence angle differences between radiometer channels were transformed in a similar manner using the partial derivatives of Tb with incidence angle derived from RTM simulations. In the second approach, we used a prediction algorithm that relies on the correlation between radiometer Tb's at various frequencies and polarizations and which uses a regression on the Tb's and their non-linear transformations developed using an independent radiative transfer model. As a demonstration, near-simultaneous pair-wise ocean Tb comparisons are presented between the TRMM Microwave Imager (TMI), which is not sun synchronous, and the sun-synchronous polar orbiting WindSat, using oceanic Tb observations from 2003-04. The corresponding results between these two inter-satellite calibration techniques are highly correlated, and results demonstrate that fixed channel-by-channel differences, of order 1-2 K exist between TMI and WindSat. These are significant radiometric calibration differences, which can be removed prior to forming joint data sets of geophysical parameter retrievals.
Keywords: Radiometers; Radiometer; Salinity SSS